POLSKA GOSPODARKA NA KWARANTANNIE – ANALIZA WSKAŹNIKÓW EKONOMICZNYCH, SPOŁECZNYCH ORAZ ROZWIĄZAŃ FORMALNOPRAWNYCH DOTYCZĄCYCH PRZECIWDZIAŁANIA KORONAWIRUSOWI COVID-19 - Staniszewski, Robert (Polityka i Społeczeństwo, 2021)
On 11th March 2020, the World Health Organization (WHO) announced the COVID-19 pandemic, i.e., SARS-CoV-2 coronavirus disease. A few days later, an epidemic emergency was announced in Poland. From the very beginning, it was obvious that the pandemic, apart from the strictly health dimension, would affect a number of aspects of the state's functioning, including the key one – its economy. The purpose of the article is to provide a multidimensional analysis of the impact of the pandemic on the state’s financial status, in particular in relation to the most fundamental economic and social indicators as well as formal and legal solutions, including so-called “anti-crisis shields” (1.0 – 4.0). Finally, analysis of the social perception of the phenomenon (public opinion) in relation to two groups, i.e., entrepreneurs and the general public, also constitutes one of the key elements of the present study.